Spectral Features of Isolated Vowels in the Subdialect of Kučiūnai - Leskauskaitė, Asta (Kalbotyra, 2000)
The article analyses the acoustic and articulative features of isolated vowels in the Kučiūnai subdialect. The vowels are compared with the corresponding vowels of the subdialect of Akmenė (North Žemaitian dialect) and Jones’ cardinal vowels.The results of the experiment have demonstrated that extreme front, back and high articulation is not peculiar to the dialect; however, its vowels have a tendency towards a rise and greater openness than cardinal vowels or the vowels of the Akmenė subdialect. Acoustically, isolated vowels are similar to both primary and secondary cardinal vowels.It will be noted that [ы.] and [ы] should be treated as front vowels, while the labial vowels are only [u], [u.], [ų.].A separate analysis is given to the isolated vowels [i.], [u.] and [į.], [ų.]. According to their qualitative features, the said vowels have close similarities; they only differ with respect to F2 meanings which show that [į.], [ų.] still preserves nasality.